An extended edge-notched disc bend (ENDB) specimen for mixed-mode I+II fracture assessments. (1st June 2020) - Bahmani, A.; Aliha, M.R.M.; Jebalbarezi Sarbijan, M.; Mousavi, S.S.
Abstract: A new test specimen for mixed-mode I+II fracture studies is proposed. An extended version of edge notch disc bend (ENDB) specimen, which was recently proposed to assess mixed-mode I+III fracture toughness, is designed and developed for introducing opening-in-plane-shear sliding mode. This new specimen that is called asymmetric ENDB specimen (A-ENDB), was numerically analysed to determine the stress intensity factors and T -stress along the crack front for a wide range of geometric and loading conditions. The finite element results demonstrated that (i) the contribution of mode III component is negligible under asymmetric loading of ENDB specimen and; (ii) the full modes I and II mixities including pure mode I, pure mode II and intermediate mode mixities can be achieved by changing loading support distances. The capability of the proposed asymmetric ENDB specimen was then experimentally assessed by conducting several mixed-mode I+II fracture toughness tests on a brittle model polymer (PMMA). The mode II fracture toughness value obtained from the A-ENDB specimen was noticeably greater than K Ic value. Although the fracture trajectory of all A-ENDB specimens was nearly self-similar and along the plane of initial crack, different fracture surface morphologies were observed for mixed-mode I+II. The fracture surface consists of mirror area and ridge markings. While, towards to pure mode II, both density and length of the ridge marking were increased. It is shown that by using the same shape test specimen, loading type, and test configuration, both mixed-mode I+II and I+III can be studied.